PENGARUH MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR FISIKA SISWA SMA - Turnip, Betty m; Sinaga, Dulas Oklana (Universitas Negeri Medan, 2016)
This research aimed to know the effect ofÂ Project Based Learning model toward physics student learning outcomesin the subject matter of dynamic elecricityin the second half of class X SMA Negeri 6 Binjai T.P. 2015/2016. This research is quasi experiment with pretest-posttest control group design, with a sample of two classes, the experimental class (X-2) and a control class (X-6) each of which is 31 students. Instruments essay test form number about 10 items and activities of students. The result showed the average value of the experimental class pretest was 46,70 and the average value of the control class is 46,58. The results of the average post-test experimental class 58,38 and control class 54,00. So it can be concluded that the results showed that the use of project based learning model of learning outcomes better than conventional learning.